Utilization herbal as a denture cleanser in inhibiting the growth of Candida albicans and Streptococcus mutans: a literature review: Pemanfaatan herbal sebagai pembersih gigi tiruan dalam menghambat pertumbuhan Candida albicans dan Streptococcus mutans: sebuah literature review - Ririn Alvianita; Mohammad Dharma Utama; Eri Hendra Jubhari (Makassar Dental Journal, 2021)
Background: Candida albicans and Streptococcus mutans are microorganisms found in denture plaque and can cause denture stomatitis. To inhibit its growth, denture users are recommended to use denture cleanser. One of the developments of denture cleanser is ingredients derived from herbs. The herbal content can be used as a denture cleanser which has low side effects and can inhibit the growth of denture plaque. Objective: To determine the effect of herbal ingredients as denture cleansers on the growth of Candida albicans and Streptococcus mutans. Method: Literature Review. Result: The content of herbal ingredients that have antifungal and antibacterial properties is found in compounds such as alkaloids, flavonoids, terpenoids, steroids, and saponins. These compounds have bactericidal and bacteriostatic effects that can inhibit the growth of Candida and Streptoccous mutans in dentures by various mechanisms. Conclusion: The herbal content has sufficient effectiveness in fighting microbial growth in dentures and it can be developed into denture cleansers.